SPEECH DISFLUENCY AS SEEN IN AUTURO GAVINO’S BEFORE ALL OTHERS KETIDAKFASIHAN BERBICARA YANG DITEMUKAN DIDALAM FILM BEFORE ALL OTHERS OLEH AUTURO GAVINO - Alo, Rosiana; Padji, Simon S; Separ, Fransiskus M (Lantern: Journal of Language and Literature, 2023)
This study aimed at determining the types of speech disfluency and the most dominant of speech disfluency as seen in Autoro Gavino’s movie Before All Others. The method used in this study was a qualitative method to determine the types of speech disfluency and the quantitative method was used to count the most frequent types found in Before All Others movie. The data in this study was taken from the Before All Others movie and the data form of utterances. The result show that there were 64 utterances showed eight types of speech disfluency in Before All Others. Those types were silent pause (13), filled pause (7), repetition (27), interjection (10), un-retraced false start (1), retraced false start (1), correction (1), and stutter (4). Meanwhile, the most frequent type of speech disfluency that appeared in Before All Others is repetition with a percentage 42.75%.